Effect of Social Media on Youth: A Study in Indian context with Reference to Rewa (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this context, "social media" means any and all online platforms that facilitate user-to-user communication, content sharing, and location-independent video conferencing, among many other features. Anyone interested in accessing information, sharing it, and chatting with other members of a certain social media platform must first register for an account and then log in. Facebook, Twitter, WhatsApp, Snapchat, and a plethora of others are among the most popular and extensively used social networking sites. There are good and bad effects of social media use on today's kids. I want to shed light on the effects of social media on today's youngsters in this article. There are benefits and drawbacks to these effects. As a result, the article lays out the pros and cons of social networking for teens. Learning new things, fostering better relationships, securing employment, maintaining global connections, and using social media as an e-commerce platform are some of the beneficial effects highlighted in this article. However, this article does acknowledge that there are negative aspects of social media, such as cyberbullying, hacking, addiction, cheating, and humiliation. In light of the claims and presentations based on the findings of earlier studies.